HUBUNGAN INDUSTRI 4.0 TERHADAP PERKEMBANGAN TEKNOLOGI PERUMAHAN: Sebuah Literature Review - Ridwana, Rifan (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
This paper discusses about industry 4.0 and housing technology from various literature studies. The literature review will provide a deep understanding of industry 4.0 and housing technology, and understand the interrelationships between the two topics by conducting theoretical dialogues to create a systematic theory. This paper is divided into three parts, part first deals with theories relating to understanding of the Industrial Revolution 4.0, second, theories that discuss about housing technology, and the third part is to analyze the linkages between industry 4.0 and housing technology. Based on literature review, it found that industry 4.0 have big impact in housing industrialization technology development by creating smart system that can be utilize to make mass and customized housing product.